LOOKING FOR THE BEST SLOGAN: AN ANALYSIS OF THE SLOGANS OF THE 2016 ROMANIAN PARLIAMENTARY CAMPAIGN - Amălăncei, Brînduşa-Mariana; Cîrtiţă-Buzoianu, Cristina; Daba-Buzoianu, Corina (Studies and Scientific Researches. Economics Edition, 2017)
The paper investigates the slogans released by political parties during the elections for the Romanian Parliament in 2016, by addressing the way they have been perceived by both political analysts and students enrolled in communication programs. We aim to see how two different target audience evaluate the slogans and how they refer to them. Also, we are interested to see what the students remember about the slogans after six months after the end of the campaign, in order to explore if their memories about the slogans had any connection with the political analysts comments made during the elections.